Technical-tactical performance and states of humor: indicators between victory and defeat in young beach volleyball athletes (Research, Society and Development, 2020)
The aim of the study was to compare performance indicators and the profile of mood states in young male beach volleyball athletes. The sample consisted of 50 athletes, with ages between from 15 to 17 years, who participated at the Youth School Games (JEJ). We filmed 16 games during the qualifying phase of JEJ, which we grouped into winners and losers. Higher scores with significant difference (p